The theatre company of francisco fructuoso dias in the province of são pedro do rio grande do sul (1845-1847) - Augusto Souza E Silva Bianchini, José [UNESP] (My University, 2022)
This paper looks at the trajectory of Francisco Fructuoso Dias' Theatre Company through the stages of Rio Grande do Sul in the 19th century. Fructuoso Dias, a Portuguese actor and regisseur, played an important role in the regeneration of Portuguese Theatre in the late 1830s. In 1843, he was hired by the main Brazilian Theatre Company in Rio de Janeiro. At the end of his contract, Fructuoso Dias set up his own company formed by Portuguese and Brazilian artists, who left for the province of São Pedro do Rio Grande do Sul shortly after the end of the Farroupilha Revolution (1835-1845). The article focuses on the company's production in the cities of Rio Grande and Porto Alegre between 1845 and 1847, to demonstrate the importance of Francisco Fructuoso Dias' Company to the 19th century theatre scene in Rio Grande do Sul.
A COMPANHIA TEATRAL DE FRANCISCO FRUCTUOSO DIAS NA PROVÍNCIA DE SÃO PEDRO DO RIO GRANDE DO SUL (1845-1847)
Keywords: Brazilian Theatre; Francisco Fructuoso Dias; Rio Grande do Sul